Popular Food Products Among Farmers in the Piedmont Triad Region of North Carolina - Okefi, Uchenna; Ejimakor, Godfrey (European Scientific Journal, ESJ, 2024)
This study evaluated the products produced by farmers in the 12-county Piedmont Triad Region of North Carolina. The study aimed to identify the most popular food products among farmers in order to enhance the local food economy. This was done by identifying food items that may be more suitable for production in the region. Survey respondents were asked to list all food items that they produced. The listed items were categorized as either crops or livestock products. The percentages of farmers that produced the different food items were calculated and compared. Beef was the number one livestock product produced by farmers in the region. Tomatoes, then lettuce, were the most predominant plant products produced by the region’s farmers. One of every six farmers in the region produced tomatoes. Beef was produced by one of every eight farmers in the region. New and beginning farmers in the region will do well by considering these products because their production by many existing farmers may imply that there is a ready market for them.